Lipid biomarkers and compound specific δ 13 C analysis indicate early development of a dual-economic system for the Arctic Small Tool tradition in northern Alaska - Buonasera, TY; Tremayne, AH; Darwent, CM; Eerkens, JW; Mason, OK (Journal of Archaeological Science, 2015)
© 2015 Elsevier Ltd. Analysis of preserved lipids from archaeological sites in northwest Alaska indicates hunters exploited marine animal resources as early as 4500 years ago. Bone preservation at early prehistoric sites in northern Alaska is generally poor, contributing to uncertainty about the economic orientation of the earliest Arctic Small Tool tradition (ASTt) hunters. We used lipid analysis and compound specific stable isotope analysis (CSIA) of burned, cemented sand and organic residue features to detect the use of marine versus terrestrial animals at several coastal sites in northwest Alaska. Though the sample size for this initial study was small (n=5), comparisons among samples from early ASTt, and later Norton and Thule sites indicate all three groups made use of marine animals for food and/or fuel. Recently obtained radiocarbon dates suggest ASTt hunters settled coastal regions of Alaska prior to moving inland to exploit terrestrial habitats. Our results provide empirical evidence that suggests the economy of the early ASTt population included a maritime component. In Arctic settings where bone preservation is poor, lipid analysis of cemented sand and organic residue features can provide an effective alternative for detecting the use and processing of marine versus terrestrial animals.